China dreams - Golley, Jane, 1971-; Jaivin, Linda; Hillman, Ben; Strange, Sharon (China story yearbook ;, 2020)
The concept of the China Dream was first coined by Xi Jinping. It describes a set of personal and national ideals. The phrase is a loan translation: it follows the rendering of the 'American Dream'.